PENGARUH LATIHAN RANGE OF MOTION AKTIF PADA LANSIA DALAM MENINGKATKAN KEKUATAN OTOT EKSTREMITAS - Annisa Nur Ikhsan; arsyawina arsyawina; Hesti Prawita Widiastuti (Poltekkes Kemenkes Kalimantan Timur, 2022)
The elderly people in East Kalimantan at 60-74 years is 4.56% from total population. The number of elderly people at Samarinda estimated in 3.3% from 988,943 total population. (DKK Samarinda, 2015). The elderly people mostly decreased in the musculoskeletal system that caused by decrease of muscle mass. Range of motion exercises are carried out regularly can increase muscle strength in clients who has impairment or limited motor function. This study aims to determine the effect of active ROM to increasing limb muscle strength in the elderly people at UPTD PTW Nirwana Puri, Samarinda. This research used quasi experiment design with pre and post test without control design. Research respondents were 12 elderly people. Data collection techniques are measurement, observation and documentation techniques. Active ROM is carried out 3 times a week with duration 30 minutes for 2 weeks. Data was analyzed using wilcoxon test. The results of this study was indicate that there have differences between muscle strength before and after ROM intervention, the right upper extremity with p = 0.01, upper left extremity with p = 0.03, lower right extremity with p = 0.02, left extremity below the value of p = 0.01. This study demonstrated effectively of active ROM intervention in increasing limb muscle strength in the elderly people. The expectation that the results of this study can be used be standard operating procedure in providing nursing care for the elderly.